Overview on Heterogeneity in Longevity and Pension Schemes - Lee, Ron; Sanchez-Romero, Miguel (World Bank, Washington, DC, 2019)
Differences in life expectancy between high and low socioeconomic groups are often large and have widened in recent decades. In the United States, the differences may now be as large as ten to fourteen years. These longevity gaps strongly affect the actuarial fairness and progressivity of many public pension systems, raising the question of possible policy reforms to address this issue. This paper reviews the empirical literature on the longevity differences across socioeconomic groups and their impacts on lifetime benefits, considers how these impacts depend on four different pay-as-you-go pension structures (calibrated on the US case), and discusses some policy options.